Comparison of bone age assessment in hand and wrist radiographs of individuals aged 12-18 using the Gilsanz-Ratib and Kahn-Gaskin atlases: a single-center study - Malkoçoğlu, Nermin; YÜCEL BEYAZTAŞ, Fatma; ATALAR, Mehmet Haydar; MALKOCOGLU, Ahmet; YILDIRIM, Ali; BÜTÜN, Celal (The Bulletin of Legal Medicine, 2025)
Objective: Age estimation is a critical component of forensic medicine. This study aimed to assess the concordance and discrepancies between age estimations derived from the Kahn Gaskin (KG) and Gilsanz Ratib (GR) atlases and individuals’ chronological ages, as well as to evaluate the agreement between these atlases and their applicability to the Turkish population.Methods: A retrospective analysis was conducted on hand and wrist radiographs of individuals aged 12–18 years who presented to Sivas Cumhuriyet University Hospital between 2019 and 2023. A total of 700 subjects (50 males and 50 females per age group) meeting the inclusion criteria were randomly selected. Bone age was assessed using the GR and KG atlases.Results: Bone age estimations based on the GR Atlas were significantly higher than chronological age in all male and female groups, except for the 18-year-old cohort. The maximum overestimation was 1.59 years in females and 0.97 years in males. Similarly, the KG Atlas indicated higher bone ages in all female groups except for 18-year-olds and in all male groups except for 15- and 18-year-olds, with overestimation reaching 0.69 years in females and 0.72 years in males.Conclusion: The findings demonstrate substantial discrepancies between estimated bone age and chronological age across atlases. To establish a population-specific bone age atlas, further large-scale, multicenter studies encompassing all seven geographical regions of Turkey are warranted.
Keywords: Bone age; Forensic medicine; Age Determination; Gilsanz Ratib Atlas; Kahn Gaskin Atlas